Pengembangan Gerak Dasar Manipulatif Berbasis Media Inovatif untuk Pembelajaran Penjas SD - Lesmawan, Hendra; Handayani, Widya; Lanos, Muhsana El Cintami; Putri, Siti Ayu Risma; Manullang, Jujur Gunawan; Tarmizi, Machiavelli Herman (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This research aims to develop an innovative media-based manipulative basic motion learning model in elementary school, with the "Rainbow Bottle" model packaged in a 4D animation video. The model includes materials, simulations, and interactive quizzes to improve students' basic motor skills. Using a 4D development research design that includes the Define, Design, Develop, and Disseminate stages, the results show that 4D animation media is effective in helping students understand and practice basic manipulative movements more clearly and interestingly. The trial at SDN 01 Tiuh Balak, Way Kanan, involved 40 students who managed to master the basic manipulative movement technique well. This model is considered feasible to be applied by experts and can improve the quality of physical education learning at the elementary level. It is hoped that this model can be disseminated and applied more widely in other schools to support more interactive and fun learning.